2017
DOI: 10.1016/j.bjan.2015.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Correlação entre a carga horária semanal de trabalho com a síndrome de burnout entre os médicos anestesiologistas de Maceió‐AL

Abstract: This study showed no correlation between the weekly working time and the BS dimensions in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
6

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 12 publications
0
1
0
6
Order By: Relevance
“…In the pooled random-effect estimates of prevalence in these 21 studies, 32% (95% CI, 27%-38%; I 2 = 95.32%; P < .001) of physicians and dentists exceeded the high threshold for emotional exhaustion, and 25% (95% CI, 18%-32%; I 2 = 98.20%; P < .001) were above the high threshold for depersonalization (Figure 2). [39][40][41][42]44,45,48,50,53,54,80,[84][85][86][87][88][89][90][91][92][93][94] In 20 studies, 33% (95% CI 22%-45%; I 2 = 99.25%; P < .001) were below the low threshold for personal accomplishment (eAppendix 4 in the Supplement). Subgroup analyses suggested that the prevalence of burnout dimensions varied depending on the country's geographical region (P for heterogeneity < .001), physician specialties (P for heterogeneity < .001), and thresholds used (emotional exhaustion and personal accomplishment: P for heterogeneity = .007; depersonalization: P for heterogeneity < .001).…”
Section: Resultsmentioning
confidence: 99%
“…In the pooled random-effect estimates of prevalence in these 21 studies, 32% (95% CI, 27%-38%; I 2 = 95.32%; P < .001) of physicians and dentists exceeded the high threshold for emotional exhaustion, and 25% (95% CI, 18%-32%; I 2 = 98.20%; P < .001) were above the high threshold for depersonalization (Figure 2). [39][40][41][42]44,45,48,50,53,54,80,[84][85][86][87][88][89][90][91][92][93][94] In 20 studies, 33% (95% CI 22%-45%; I 2 = 99.25%; P < .001) were below the low threshold for personal accomplishment (eAppendix 4 in the Supplement). Subgroup analyses suggested that the prevalence of burnout dimensions varied depending on the country's geographical region (P for heterogeneity < .001), physician specialties (P for heterogeneity < .001), and thresholds used (emotional exhaustion and personal accomplishment: P for heterogeneity = .007; depersonalization: P for heterogeneity < .001).…”
Section: Resultsmentioning
confidence: 99%
“…No tocante a carga horária de trabalho, uma pesquisa desenvolvida em três hospitais públicos e dois privados com 43 anestesiologistas em Maceió -Alagoas (AL) concluiu que nenhuma correlação foi vista entre carga horária e as dimensões de burnout, concordando com o resultado de outro estudo feito com médicos intensivistas de Maceió (BARBOSA FT, et al, 2017). Com isso, esse trabalho excessivo tanto está associado a SB como também aos erros médicos, pois viu-se que os profissionais com alta carga horária e/ou acometidos por SB tendem a errar mais (HOELZ L e CAMPELLO L, 2015).…”
Section: Titulaçãounclassified
“…Al aproximarnos al contexto sociopolítico de la región de La Araucanía es la que presenta históricamente los indicadores biomédicos y sociales más deteriorados del país: alta ruralidad, años de vida potencialmente perdidos, y los índices de pobreza y pobreza extrema más altos del país, con un 27,9% y 10,6% respectivamente 8,9 . Estos elementos configuran las particularidades de los pacientes de la Región, a ello se agrega el rol de cada profesional como los anestesiólogos dedicados al alivio del dolor y al cuidado del paciente quirúrgico antes, durante y después del acto quirúrgico, también el soporte del paciente crítico en urgencias y la participación en cuidados paliativos 10 . El rol de la traumatología abarca más allá del campo de lesiones traumáticas; contempla también el estudio de patologías congénitas y cáncer.…”
Section: Introductionunclassified